Aberrant expression of the p53 oncoprotein is a common feature of a wide spectrum of human malignancies - Bártek, J; Bártková, J; Vojtĕsek, B; Stasková, Z; Lukás, J; Rejthar, A; Kovarík, J; Midgley, C A; Gannon, J V; Lane, D P (Oncogene, 1991)
Accumulation of the p53 protein was analysed in 212 human malignant lesions. Immunohistochemical staining with new polyclonal (CM-1) and monoclonal antibodies (BP 53-12 and BP53-24) to p53 on methacarn-fixed paraffin sections showed positive staining in 161 (76%). The positive tumours were found across a wide range of human malignancies including breast, colon, stomach, bladder and testis carcinomas, soft-tissue sarcomas and melanomas. The staining was always confined to the malignant lesion. Immunoprecipitation and quantitative ELISA assays established that the positive staining was associated with accumulation of the protein and that the protein was frequently in a mutant conformation. Accumulation of mutant p53 protein is therefore a common feature of human malignant disease.
Keywords: exprese genu; Humans; Gene Expression; Genes, p53; nádorový supresorový protein p53; geny p53; Antibodies, Monoclonal; mutace; Female; ELISA; lidé; Immunohistochemistry; imunohistochemie; Enzyme-Linked Immunosorbent Assay; transfekce; ženské pohlaví; protilátky; Neoplasms; Antibodies; monoklonální protilátky; nádory; Transfection; Mutation; Tumor Suppressor Protein p53